Taking Stock, December 2015 : An Update on Vietnam's Recent Economic Developments - World Bank (Hanoi, 2015)
Vietnam’s economy has weathered the recent turbulence in the external environment fairly well, reflecting resilient domestic demand and robust performance of export-oriented manufacturing. Growth further accelerated to 6.5 percent (year-on-year) in the first three quarters of 2015 (after coming in at 6 percent last year). Low inflation and strengthening consumer confidence supported an uptick in private consumption while investment was lifted by robust foreign direct investment, rising government capital expenditures, and a recovery of credit growth. Exports of the foreign-invested manufacturing sector also accelerated, but this was offset by a slowdown of commodity exports and a surge in imports of capital and intermediate goods, reflecting stronger investment and the high import content of manufacturing exports.